The Effect of Job Flexibility and Job Burnout on Turnover Intention - Thoyibah, Vike Mawadathan; Desiana, Putri Mega (Universitas Hamzanwadi, 2024)
Job flexibility and job burnout are one of the reasons why employees choose to resign from the workplace which ultimately causes turnover in the company. This study aims to test, analyze, and prove the effect of job flexibility and job burnout on employee satisfaction and its relationship with turnover in startup companies. This study method applied quantitative research design. The data were collected through electronic surveys addressed to 155 startup employees who get job flexibility from the company. The results showed that job flexibility has a positive effect on job satisfaction and a negative effect on turnover intention. Then, job burnout has a negative effect on job satisfaction and a positive effect on turnover intention. In addition, job satisfaction can mediate job flexibility and job burnout on turnover intention